Respuesta :
2x – y = 2
–x + 5y = 3
This is a system of equations. I will use substitution.-x + 5y = 3
-x = 3 - 5y
x = 5y - 3
2x -y = 2 (substitute the top part into here)
2(5y-3) - y = 2
10y - 6 - y = 2
9y = 8
y = 8/9
x = 5y - 3 = 5(8/9) - 3 = 13/9 = 1.444444 repeating Since there is a solution of (13/9, 8/9), there is 1 solution
The answer is A. Keep in mind, answer choice C is impossible; you can never have a system of equations with 2 solutions :)
x = 5y - 3 = 5(8/9) - 3 = 13/9 = 1.444444 repeating Since there is a solution of (13/9, 8/9), there is 1 solution
The answer is A. Keep in mind, answer choice C is impossible; you can never have a system of equations with 2 solutions :)